Visão prospectiva: tendências e perspectivas futuras na indústria de alimentos - Nóbrega, Thainara Cardoso (Universidade Federal de São Carlos, 2024)
The food industry is a dynamic sector in constant evolution, characterized by the adoption of new production methods, innovations in ingredients, and the release of new products. One of the primary driving forces behind these changes is the increasing demands of consumers, who continually seek improvements in terms of taste, quality, and nutritional value of food. To meet these demands and ensure customer satisfaction, companies employ various strategic tools to stay ahead in the market and innovate their products. This entails understanding consumer expectations and desires, not only regarding the products themselves but throughout the entire production chain, from raw materials to final consumption. The aim of this study was to analyze current trends in the food market through a literature review. The intention is to create an informative and comprehensive material on market trends and projections, aiming to provide insights for future innovation projects and research in the food industry. During the analysis process, it became evident that consumer demands have been recognized and implemented in the production chain, both in large industries and startups. Issues such as ingredient and production process sustainability have been considered, maintaining a focus on quality and often substituting ingredients for healthier options. Concluding, there's a quest for new food sources, primarily driven by environmental concerns and the growing world population, emphasizing nutritional quality and formulation improvements.
Prospective vision: trends and future perspectives in the food industry
Keywords: Inovação; Qualidade; Saudabilidade; Innovation; Quality; Healthiness; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS